AN EVALUATIVE STUDY OF THE OPERATIONAL EFFICACY OF MSME’s IN PALANGKA RAYA UTILIZING THE K-MEANS CLUSTERING ALGORITHM - Jonathan Giovanni; Pratiwi Subianto; Alicia Christina Mahar; Fricella Aprianda (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This study aims to categorize MSMEs in Palangka Raya City based on their performance and competitiveness using the K-Means Clustering methodology.Design/Methodology/Approach – Data were collected through surveys of 100 MSMEs, focusing on financial performance, product sales, and marketing strategies, and analyzed using KNIME software to create homogeneous clusters.Findings – The analysis identified three distinct clusters of MSMEs: those with high product diversity, strong financial stability, and emerging MSMEs, each with unique attributes for targeted strategy formulation.Conclusion and Implications – The study provides strategic recommendations for local governments to enhance MSME competitiveness and foster sustainable economic growth through tailored programs and initiatives.